CD4+ T cell activation and inflammation in NASH-related fibrosis - Zhou, Yunfeng; Zhang, Haibo; Yao, Yao; Zhang, Xiaoyan; Guan, Youfei; Zheng, Feng (Frontiers in Immunology, 2022)
Liver fibrosis is a common pathological feature of end stage liver failure, a severe life-threatening disease worldwide. Nonalcoholic fatty liver disease (NAFLD), especially its more severe form with steatohepatitis (NASH), results from obesity, type 2 diabetes and metabolic syndrome and becomes a leading cause of liver fibrosis. Genetic factor, lipid overload/toxicity, oxidative stress and inflammation have all been implicated in the development and progression of NASH. Both innate immune response and adaptive immunity contribute to NASH-associated inflammation. Innate immunity may cause inflammation and subsequently fibrosis via danger-associated molecular patterns. Increasing evidence indicates that T cell-mediated adaptive immunity also provokes inflammation and fibrosis in NASH via cytotoxicity, cytokines and other proinflammatory and profibrotic mediators. Recently, the single-cell transcriptome profiling has revealed that the populations of CD4+ T cells, CD8+ T cells, γδ T cells, and TEMs are expanded in the liver with NASH. The activation of T cells requires antigen presentation from professional antigen-presenting cells (APCs), including macrophages, dendritic cells, and B-cells. However, since hepatocytes express MHCII molecules and costimulators, they may also act as an atypical APC to promote T cell activation. Additionally, the phenotypic switch of hepatocytes to proinflammatory cells in NASH contributes to the development of inflammation. In this review, we focus on T cells and in particular CD4+ T cells and discuss the role of different subsets of CD4+ T cells including Th1, Th2, Th17, Th22, and Treg in NASH-related liver inflammation and fibrosis.